2011
DOI: 10.1007/s00018-011-0699-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of γδ T cell responses by TLR ligands

Abstract: Toll-like receptors (TLR) are pattern-recognition receptors that recognize a broad variety of structurally conserved molecules derived from microbes. The recognition of TLR ligands functions as a primary sensor of the innate immune system, leading to subsequent indirect activation of the adaptive immunity as well as none-immune cells. However, TLR are also expressed by several T cell subsets, and the respective ligands can directly modulate their effector functions. The present review summarizes the recent fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 110 publications
6
99
1
1
Order By: Relevance
“…This is somewhat akin to the jawed vertebrate immune system, where (for example) flagellin perception by its cognate PRR can potentiate adaptive immunity in T cells (35). Pathogens such as P. syringae have associated with them multiple PAMPs (e.g., lipopolysaccharide, elongation factor Tu, and flagellin) (2), which upon recognition by plant cells, could individually raise an alarm and evoke a Ca 2+ burst (2,6,26) necessary for the activation of immune signaling cascades leading to HR.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat akin to the jawed vertebrate immune system, where (for example) flagellin perception by its cognate PRR can potentiate adaptive immunity in T cells (35). Pathogens such as P. syringae have associated with them multiple PAMPs (e.g., lipopolysaccharide, elongation factor Tu, and flagellin) (2), which upon recognition by plant cells, could individually raise an alarm and evoke a Ca 2+ burst (2,6,26) necessary for the activation of immune signaling cascades leading to HR.…”
Section: Discussionmentioning
confidence: 99%
“…36 Interestingly, it has been reported that gd T cells, in contrast to ab T cells, may themselves possess TLRs. 37 However, it has not yet been analyzed whether the ICDassociated TLR-binding of DAMPs might be directly activating gd T cells thereby partly bypassing the DC-T cell interaction route. This represents an attractive possibility that needs further analysis.…”
Section: Introduction To Immunogenic Cell Deathmentioning
confidence: 99%
“…TLR1 and TLR6 usually form heterodimers with TLR2 (53), and TLR2 activation has been shown to inhibit early TLR9 and TLR7 induction of IFN-␤ mRNA (54).…”
Section: Discussionmentioning
confidence: 99%